Advances in research and adaptive expressions of entitlement: a mini review - George-Levi, Sivan (Frontiers in Psychology, 2025)
Entitlement, often defined as the belief in deserving special treatment or outcomes, has traditionally been seen as a pathological trait closely tied to narcissism and interpersonal dysfunction. However, accumulating evidence shows that entitlement is multidimensional and context-sensitive, with the potential to operate in both adaptive and maladaptive ways. This mini-review synthesizes advances across personality and social psychology, highlighting four developments: (a) recognition of distinct forms of entitlement, ranging from exploitative and inflated to active, assertive, and emotionally balanced; (b) growth of domain-specific research in relational, workplace, academic, and emotional contexts; (c) evidence that entitlement is activated by situational cues such as fairness, injustice, and life stress; and (d) identification of moderators that buffer risks and channel entitlement into constructive expressions. The findings indicate that the definition of entitlement has expanded beyond its original formulation, revealing a construct more complex than previously assumed, with empirical evidence showing varied and sometimes contradictory outcomes. Future research should prioritize multi-faceted and domain-targeted measures, employ longitudinal and experimental designs to clarify mechanisms, and apply integrative models that distinguish entitlement’s bright sides from its dark sides. These insights also hold practical relevance for education, organizations, relationships and therapeutic practice, where differentiating adaptive from maladaptive entitlement can guide more effective interventions.